The Influence of Leadership and Organizational Culture on Employee Performance Through Organizational Commitment as an Intervening Variable at CV. Terus Jaya, East Lombok Regency - Irmayani, Dian Susmilayatul; Sulaimiah, Sulaimiah (Universitas KH. Abdul Chalim Mojokerto, 2026)
This research aims to analyze the influence of leadership and organizational culture on employee performance through organizational commitment as an intervening variable at CV. Terus Jaya, East Lombok Regency. The study was motivated by the importance of leadership and a strong organizational culture in improving employee performance within a staple goods distribution company. The research problems focus on determining both the direct and indirect effects of leadership and organizational culture on employee performance mediated by organizational commitment. The study employed a quantitative survey method by distributing questionnaires to all employees, with a sample of 59 respondents selected from a total population of 134 employees. Data were analyzed using path analysis through SmartPLS 4.0 software. The results showed that leadership and organizational culture had a positive and significant influence on employee performance, both directly and indirectly, through organizational commitment. Furthermore, organizational commitment served as a significant mediating variable that strengthened the relationship between leadership, organizational culture, and employee performance. The findings emphasize the strategic role of leadership and cultural values in enhancing employee commitment and overall organizational effectiveness.